CARA K.H. AHMAD DAHLAN MENCARI KEBENARAN TERHADAP EPISTIMOLOGI BARAT - mul yati (Rausyan Fikr : Jurnal Pemikiran dan Pencerahan, 2022)
BSTRACT: Kyai Ahmad Dahlan is indeed a charitable person. He is not just thinking, and understanding the problem. But more importantly, he thinks far ahead, and looks for fundamental problem solutions. Even more than that, Kyai Dahlan directly led the struggle itself; made himself, his wife, and his family a role model for struggle. Despite being colonized economically, politically, and militarily, Kyai Dahlan understands well that the root of the problems of the people and the nation lies in the problem of education. From this education will be born cadres of the people and the nation. It is recognized that the philosophical way of thinking has broken down the doors and walls of traditions and customs, and has even uncovered myths and abandoned mystical ways of thinking. The same thing has also succeeded in developing ways of thinking rationally and deeply, integrally and coherently, methodically and systematically, logically, critically, and analytically. Therefore, science is growing, growing and maturing. Thoughts K.H. Ahmad Dahlan on Islamic education is closer to Perennial Philosophy thinking. Islamic education is more colored by its religious spirit by developing integrative, cooperative, accommodating and comprehensive education with special characteristics of monotheism and universality of knowledge as the content of education (curriculum), Akhlaqul karimah as the basis for educational goals, affective intelligence (attitude), cognitive (brain) and psychomotor (motion) as a development step, so as to avoid fatalism and ambivalence. In the study of epistemology, it gives birth to a clear concept of science to be realized into a comprehensive educational curriculum, without separating the empirical sciences (aqli) and the diniyah sciences (naqli). The axiological approach gives birth to views that are always in the value corridor. The operational appearance of education is not only used as a vehicle for the preservation (maintaining) of religious values, but more than that as a center and a means of developing knowledge, which is operated in an adapted, eclectic, cooperative, contextual, actual and universal manner and relies on intuition.